2019
DOI: 10.9734/ijtdh/2019/v37i430170
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Level of Patient Activation and Its Role to Glycemic Control and among Adults with Type II Diabetes Attending Diabetic Clinic at Hospitals in Addis Ababa

Abstract: Introduction: Lifestyle interventions as supper arranging and exercise assume a significant job in a Diabetes Self-Management Education (DSME) program. The impact of poly-pharmacy on way of life changes, for example, nourishment and exercise isn't surely known. Deciding and evaluating patient's dimension of enactment and its association with physical action level, supper arranging, and poly-pharmacy in patients with Type II diabetes is a significant standard for Diabetes Self-Management mediations.            … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 22 publications
(33 reference statements)
1
8
0
Order By: Relevance
“…27 The proportion with high activation level among patients with diabetes in Ethiopia was even lower at 24.4%. 46 Comparatively, the percentage of patients with high activation level was higher at 65.1% among frequent users of primary health care services in Canada. 47 Variations in the activation levels in the various populations could be explained by the differences in the comorbidities, cultural background, and the health care…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…27 The proportion with high activation level among patients with diabetes in Ethiopia was even lower at 24.4%. 46 Comparatively, the percentage of patients with high activation level was higher at 65.1% among frequent users of primary health care services in Canada. 47 Variations in the activation levels in the various populations could be explained by the differences in the comorbidities, cultural background, and the health care…”
Section: Discussionmentioning
confidence: 90%
“…7 Various other factors such as social support, patient-physician relationship and health literacy have been associated with patient activation levels. 46,[51][52][53] However, these were beyond the scope of our study. Analyzing the complex paradigm of human behaviors and the interaction of different mediators of self-management is also beyond the scope of this study.…”
Section: Discussionmentioning
confidence: 96%
“…In terms of the studies included in estimating the good prevalence of glycemic control, the lowest proportion (17.8%) was reported in a study conducted among T2DM patients in Addis Ababa, whereas the highest prevalence (71%) was reported in a study conducted in SNNP among both diabetic cases. Similarly, the lowest and highest rates of poor glycemic control were 29% 24 and 82%, 25 respectively. In this study, 43 articles were cross sectional studies and 4 (2 each) were cohort 48 , 56 and case control studies.…”
Section: Resultsmentioning
confidence: 97%
“…Poor glycemic control, for example, ranges from 29% 24 to 82.2%. 25 A meta-analysis of 16 studies found that only one-third of patients have good glycemic control. 26 As a result, aggregated evidences about the magnitude of poor or good glycemic control, as well as potential factors associated with poor glycemic control, are scarce in Ethiopia.…”
Section: Introductionmentioning
confidence: 99%
“…The nding is in line with the study in Australia (24) and China (26). But study in Ethiopia showed no signi cant association between duration of diagnosis and engagement in health care decision making (27).…”
Section: Discussionmentioning
confidence: 94%